Experimental investigation of the engineering constants of architectural coated fabric under uniaxial and biaxial loading - Junhao Xu; Yingying Zhang; Yushuai Zhao; Lingyu Sheng; Shuhuan Fei (Journal of Engineered Fibers and Fabrics)
The mechanical properties of coated fabric demonstrate significant material nonlinearity. Presently, testing methods to determine the engineering constants of coated fabric include uniaxial loading and biaxial loading. However, the engineering constants obtained through these methods often differ. This paper presents experimental investigations into the uniaxial and biaxial mechanical properties of architectural coated fabric. Initially, the elastic modulus and Poisson effect of the coated fabric under uniaxial tension are determined using non-contact measurement techniques. Subsequently, the influence of different stress ratio combinations on the engineering constants of coated fabric is explored through biaxial tensile testing. Finally, biaxial shear tests are conducted on architectural coated fabric to examine the effects of prestress and shear stress amplitude on the shear modulus. The results indicate that the orthogonal linear elastic model under the plane stress framework provides a high fitting accuracy for the biaxial tensile test data of coated fabric, with a maximum fitted RSS of 0.0843. Additionally, the calculated elastic modulus depends on the selection of the stress ratio group. The elastic modulus derived from the biaxial tensile test is smaller than that obtained from the uniaxial tensile test. Furthermore, the shear modulus of the coated fabric shows a linear positive correlation with the initial pretension value and decreases as the shear stress amplitude increases.